2017
DOI: 10.1080/2162402x.2017.1385690
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Tim-3 binding to phosphatidylserine and CEACAM1 is a shared feature of anti-Tim-3 antibodies that have functional efficacy

Abstract: Both data in preclinical cancer models and data with T cells from patients with advanced cancer support a role for Tim-3 blockade in promoting effective anti-tumor immunity. Consequently, there is considerable interest in the clinical development of antibody-based therapeutics that target Tim-3 for cancer immunotherapy. A challenge to this clinical development is the fact that several ligands for Tim-3 have been identified: galectin-9, phosphatidylserine, HMGB1, and most recently, CEACAM1. These observations r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 24 publications
(44 reference statements)
2
81
1
Order By: Relevance
“…CEACAM1-TIM-3 interactions have been biochemically mapped to the GFCC'C" interface of both molecules that overlaps with those involved in homophilic binding of CEACAM1 and the phosphatidylserine binding sites on TIM-3 [15,24,142]. Interestingly, the binding epitope of anti-TIM-3 antibodies that function as effective anti-cancer agents map to the CEACAM1 binding site on TIM-3 suggesting that targeting TIM-3 requires disabling TIM-3 interactions with CEACAM1 and/or phosphatidylserine [143]. Notably, a single nucleotide polymorphism in TIM-3 that causes a substitution at residue 101 (T101I) maps outside the CEACAM1-TIM-3 binding interface but is associated with an increased risk of inflammatory bowel disease [15].…”
Section: Ceacam1 Regulates T Cell Activation and Mediates Tolerance-mentioning
confidence: 99%
“…CEACAM1-TIM-3 interactions have been biochemically mapped to the GFCC'C" interface of both molecules that overlaps with those involved in homophilic binding of CEACAM1 and the phosphatidylserine binding sites on TIM-3 [15,24,142]. Interestingly, the binding epitope of anti-TIM-3 antibodies that function as effective anti-cancer agents map to the CEACAM1 binding site on TIM-3 suggesting that targeting TIM-3 requires disabling TIM-3 interactions with CEACAM1 and/or phosphatidylserine [143]. Notably, a single nucleotide polymorphism in TIM-3 that causes a substitution at residue 101 (T101I) maps outside the CEACAM1-TIM-3 binding interface but is associated with an increased risk of inflammatory bowel disease [15].…”
Section: Ceacam1 Regulates T Cell Activation and Mediates Tolerance-mentioning
confidence: 99%
“…It has been shown that functionally efficacious anti-murine and anti-human TIM-3 antibodies interfere with binding to both PtdSer and CEACAM1, 12 although none of the anti-TIM -3 antibodies tested by Sabatos-Peyton et al (2017) interfered with the binding of TIM-3 and Gal-9. However, Gal-9 has been hypothesized to be trafficked by TIM-3 and play an important role in TIM-3 signaling.…”
Section: Introductionmentioning
confidence: 98%
“…However, Gal-9 has been hypothesized to be trafficked by TIM-3 and play an important role in TIM-3 signaling. 12,13 Gal-9 also has a role in the inhibition of T cell responses 4 and may increase tumorgenicity via T cell dysfunction. 9,14 Therefore, anti-tumor efficacy could potentially be improved if the interaction of TIM-3 with Gal-9 were blocked in addition to the interaction of TIM-3 with PtdSer and CEACAM1.…”
Section: Introductionmentioning
confidence: 99%
“…TIM-3 mediates its suppressive activity on immune cells via its ligands that include phosphatidylserine, CEACAM-1 and the widely expressed ligand galectin-9 23,24 . TIM-3 is expressed on activated T cells and its signaling on cytotoxic T cells leads to an exhausted phenotype, characterized by a reduction in proliferation, decreased production of effector cytokines and apoptosis of effector T cells 25 .…”
Section: Introductionmentioning
confidence: 99%